Modelling anti-inflationary monetary targeting: with an application to Romania - Marcelo Sánchez (European Central Bank (ECB), 2010)
This paper attempts to characterise an anti-inflationary monetary targeting (MT) regime. In order to derive a formal representation of this regime, we formulate the central bank's optimisation problem under the assumption that it is possible for the monetary targeted variable to have an impact on inflation. We apply a rather general framework to the Romanian experience with MT in the period 1999-2005. We find that during this period Romania's MT regime can be characterised by a concern for price stability and an additional role for smoothing of the central bank's instrument (base money growth). Our results suggest that exchange rate variability and output gap stability appear not to have entered the objective function significantly.
Keywords: E52; E58; C32; C61; 330; Monetary Targeting; optimal monetary policy; Romania; Inflationssteuerung; Geldpolitik; Preisstabilität; Rumänien